2011
DOI: 10.3324/haematol.2011.058289
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of acute myeloid leukemia harboring monosomal karyotype in patients treated with or without allogeneic hematopoietic cell transplantation after achieving complete remission

Abstract: ABSTRACTof MK, the present analysis focused on patients who achieved CR with one or two courses of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…(2) Uneven geographic distribution of nonrandom chromosome aberrations in malignant disorders and ethic differences could be another possible explanation. Recently, Masamitsu Y et al reported MK was noted in 4% patients of Japanese AML patients who had achieved complete remission (Yanada et al, 2012). Given MK+ AML patients had a lower CR rate than MK-patients, the incidence of MK among newly diagnosed Japanese AML patients might be similar with that in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(2) Uneven geographic distribution of nonrandom chromosome aberrations in malignant disorders and ethic differences could be another possible explanation. Recently, Masamitsu Y et al reported MK was noted in 4% patients of Japanese AML patients who had achieved complete remission (Yanada et al, 2012). Given MK+ AML patients had a lower CR rate than MK-patients, the incidence of MK among newly diagnosed Japanese AML patients might be similar with that in our study.…”
Section: Discussionsupporting
confidence: 88%
“…We speculated that the dismal outcome of MK+CK+ patients in our study might be partly due to their lower CR rate than MK-CK+ group, although the difference was not statistically significant. In addition, inferior OS of MK+ AML patients can also be explained by a high risk of relapse of AML (Yanada et al, 2012). To further determine the implication of MK in response to induction therapy and RFS, a larger series of cases need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, we agree that SCT should be considered for all AML patients harbouring a MK. Comparing to other studies, we have only included here patients in CR1 which is significantly associated with a better outcome [9,10,23]. However, we have to assume a selection bias, because only patients who were fit enough to survive to the point of being eligible for allogeneic SCT have been included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This benefit should rely at least in part on a potential graft-versus-leukemia effect (GvL) in MK AML. 1 Nevertheless, if SCT can improve survival in the presence of a MK, this benefit remains limited with an estimated long-term survival after SCT of only 20 2 30% [9,10,12]. Therefore, efforts have to be made to improve outcome in MK AML after SCT either with pre-and/or posttransplantation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…An allogeneic HSCT is almost a prerequisite for prolonged survival in patients with unfavourable cytogenetic risk Stelljes et al, 2011). Younger patients with 11q23 aberrations also benefit from an allogeneic HSCT , while the beneficial effect in patients with monosomal karyotype is marginal Yanada et al, 2012). In donor versus no donor meta-analyses of younger patients with AML, patients with non-favourable cytogenetic risk and younger patients below the age of 35 years benefitted from a donor over no available donor (Cornelissen et al, 2007;Koreth et al, 2009).…”
Section: Postremission Therapy In Patients In Cr After Induction Therapymentioning
confidence: 99%